Pengaruh Gaya, Minat, Lingkungan, dan Kemandirian Belajar Terhadap Prestasi Belajar Matematika Siswa Kelas VIII UPTD SMP Negeri 5 Kupang dengan Menggunakan Path Analysis - Ahmad, Sya'ban; Ekowati, Krisnandari; Atrik Halim, Fransiska (Pendidikan Matematika FKIP Universitas Mataram, 2024)
The low learning achievement of students in class VIII UPTD SMP Negeri 5 Kupang in mathematics was the motivation for this research. The aim of this research is to ascertain whether learning style, learning interest, learning environment, and independent learning have a direct impact on mathematics learning achievement. Additionally, it seeks to ascertain whether learning style, learning interest, and learning environment have an indirect on mathematics learning achievement through independent learning. This type of research is quantitative research with survey method. This research was conducted at UPTD SMP Negeri 5 Kupang. The population in this research were all 8th grade students of UPTD SMP Negeri 5 Kupang in the 2023/2024 school year consisting of 10 classes. The sample taken was 2 classes consisting of 60 students using purposive sampling technique. Data collection techniques using questionnaires and documentation. The data analysis technique used is the classical assumption test and path analysis. The results of this research, namely (1) Learning style, learning interest, learning environment, and independent learning have a significant impact directly on mathematics learning achievement. (2) Learning style, learning interest, and learning environment have no significant indirect impact on mathematics learning achievement through independent learning.